Anomalous Aortic Origin of a Coronary Artery Repair Through an Anterior Minithoracotomy. Issue 5 (September 2021) - Nellis, Joseph R.; Drysdale, Nicolas D.; Evans, Megan A.; Habermann, Alyssa C.; Meza, James M.; Andersen, Nicholas D.; Daneshmand, Mani A.; Turek, Joseph W.
Objective: The benefits of minimally invasive adult cardiac surgery are well established. Nevertheless, minimally invasive congenital cardiac procedures, even for adult patients, are uncommon. In 2018, we started repairing anomalous aortic origin of a coronary artery (AAOCA) through a 5 cm anterior minithoracotomy when possible to improve cosmesis and avoid sternal precautions. We hypothesized this approach was safe and reliable. Methods: A 5 cm incision was made in the right second intercostal space. The incision was carried down to the pericardium while preserving the internal mammary artery. With the pericardium in view, the second and third ribs were disarticulated. Central cardiopulmonary bypass was established, and the repair was carried out based on the patient's anatomy. The technique was modified to a left anterior minithoracotomy for 1 patient who required pulmonary artery translocation. At any point, if the dissection or repair was not progressing appropriately, the minimally invasive exposure was converted to a partial or traditional median sternotomy. Results: Between June 2018 and June 2019, 11 patients underwent minimally invasive anomalous coronary repair. Four patients (3 with body mass index >30) were converted to traditional sternotomy due to poor visualization. Postoperatively, 1 patient required coronary artery bypass after 335 days, due to extensive collaterals and stable angina. Otherwise, at a median follow-up of 437 days (IQR 340 to 480), patients had resumed baseline activity without recurrent symptoms. Conclusions: Minimally invasive AAOCA repair may be appealing, although surgeons should be cautious given the high conversion rate.